Plant and Bacterial Cellulose: Production, Chemical Structure, Derivatives and Applications - Davi Texeira Reis; Anna Karla dos Santos Pereira; Gessiel Newton Scheidt; Douglas Henrique Pereira (Orbital: The Electronic Journal of Chemistry, 2019)
Cellulose is one of the most abundant biopolymers in nature. It is used in the industry in various ways, in both its original and modified forms and the latter are called cellulose derivatives. These derivatives are used in several industrial such as the pharmaceutical, food, cosmetics and can be used in solid or semi-solid form. An important application that has been currently clarified is the use of some types of cellulose derivatives as adsorbents for both metal ions and other molecules. An example is the decontamination of wastewater, as with the industrial development, some water sources are compromised and decontamination by conventional means is often not enough, hence the need for new techniques. The main advantage of using natural polymers is that they are biodegradable, because it is extremely important that a product disappear after fulfilling its purpose. An example of a natural polymer is cellulose synthesized by bacteria, also known as bacterial cellulose (BC). It has been the subject of several studies in the last decade, mainly due to the fact that it is a highly pure polymer, which makes their physical and chemical properties very different from those of plant cellulose, and also because it is easy to produce, with yields varying from one bacterium to another. The aim of this paper was to gather general information about the structures, production mode, synthesis and industrial applications of bacterial, vegetable and cellulose derivatives.DOI: http://dx.doi.org/10.17807/orbital.v11i5.1349